Pembelajaran Konvensional dan Kritis Kreatif dalam Perspektif Pendidikan Islam - Fahrudin Fahrudin; Ansari Ansari; Ahmad Shofiyuddin Ichsan (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This research aims to determine the perspective of Islamic education about conventional learning and critical creative learning. This research is library research and data collection uses documentation method. The data analysis uses a comparative technique, namely researching the philosophical foundations of conventional learning and critical-creative learning and looking at the two learning concepts using the perspective of Islamic education. Islamic education is the process of changing individual behavior in personal life and society through the learning process with an effort to help develop students to be more advanced based on good values in their lives, so that personal human beings are formed, both related to reason, feelings, and actions. The results of this research indicate that the two learning models above are very different conceptually, so there needs to be a creative unification effort from a teacher as a regulator in the learning process. Therefore, the two learning models could be useful according to the conditions and situations, so that there is no need to eliminate the conventional and critical creative learning models. Even learning with this model is very appropriate to the present.